Gelatin promotes murine fibrosarcoma L929 cell detachment and protects the cells from TNFα-induced cytotoxicity. (3rd July 2016) - Wang, Hong-Ju; Li, Meng-Qi; Liu, Wei; Yao, Guo-Dong; Xia, Ming-Yu; Hayashi, Toshihiko; Fujisaki, Hitomi; Hattori, Shunji; Tashiro, Shin-ichi; Onodera, Satoshi; Ikejima, Takashi
ABSTRACT: Purpose : Gelatin has been considered to exist as intermediate substance of collagen catabolism in tissue remodeling or under inflammatory conditions. We have initiated the study on possible biological functions of gelatin that can exist temporally and locally under the conditions of remodeling and inflammation Materials and methods : To this purpose, we investigated cell proliferation and survival on gelatin-coated dishes and the response to tumor necrosis factor α (TNFα)–induced cytotoxicity in L929 cells. Autophagy level, ATP level, and ROS generation are examined. Results : L929 cells detached from the gelatin-coated dishes and formed multicellular aggregates. TNFα-induced cytotoxicity in L929 cells was inhibited by gelatin-coating culture. The cells on gelatin-coated dishes showed reduced cellular ATP levels and increased adenosine 5′-monophosphate (AMP)–activated protein kinase (AMPK) phosphorylation, leading to increased ROS generation and autophagy. Conclusion : This study showed that gelatin-coated culture protected L929 cells from TNFα-induced cytotoxicity and suggested for a possible pathophysiological function of gelatin in regulating cellular functions.